Laundry Service Processing Website Using the RAD Method (Case Study: Berkah Laundry - Southeast Aceh) - Syarijal Alas Pagan; Cut Mutia; Julaiha Julaiha; Sanjaya Alacsel (STMIK Methodist Binjai, 2026)
Berhak Laundry is a laundry service business in Southeast Aceh Regency that requires a more structured service mechanism for presenting service information, receiving orders, arranging pickup and delivery, and providing customers with clear laundry status. Direct communication-based services may cause inconsistent records, repeated questions, delayed confirmation, and difficulties in tracking orders. This study aims to develop a laundry service website using Rapid Application Development so that user requirements can be translated through prototypes and iterative improvements. The research stages include requirements planning, user design, construction, and cutover. Requirements were collected through service-flow observation, interviews with the manager, and examination of transaction documents. The resulting website contains service information, price lists, ordering, pickup and delivery options, status tracking, order management, and transaction reporting modules. Testing of ten major functions showed that all scenarios produced the expected outputs. Prototype evaluation also indicated that navigation structure, form completeness, and status information became clearer after three improvement iterations. The developed website helps customers obtain service information and monitor their laundry process, while the manager can control order data more systematically and efficiently.